The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.12659/ajcr.920489
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cell Myeloma with an Aggressive Clinical Course and Anaplastic Morphology in a 22-Year-Old Patient: A Case Report and Review of Literature

Abstract: Unusual clinical course Background: Plasma cell myeloma is a neoplastic plasma cell disorder that usually presents after the fifth decade of life; it is rarely described in younger population especially under 30 years of age. However, there are conflicting reports in the literature about the clinical behavior and overall survival in younger age groups. In approximately 2% of plasma cell myeloma, the morphology of the neoplastic cells is highly pleomorphic, quite anaplastic, and may resemble metastatic tumor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Therefore, a new line of chemotherapy [cisplatin, doxorubicin, etoposide, cyclophosphamide] combined with pomalidomide and Carfilzomib was started for two cycles the patient planned for ASCT. 1, cases [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Upon an extensive review of English literature, a total of 22 cases of PCNs (including the three cases reported here) showed aberrant co-expression of Tcell associated markers.…”
Section: Results Results Of Patients Diagnosed In Our Centermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a new line of chemotherapy [cisplatin, doxorubicin, etoposide, cyclophosphamide] combined with pomalidomide and Carfilzomib was started for two cycles the patient planned for ASCT. 1, cases [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Upon an extensive review of English literature, a total of 22 cases of PCNs (including the three cases reported here) showed aberrant co-expression of Tcell associated markers.…”
Section: Results Results Of Patients Diagnosed In Our Centermentioning
confidence: 99%
“…16 Moreover, anaplastic myeloma variant, in which the malignant PCs are highly pleomorphic, has been reported more common in younger patients with a predisposition for the extramedullary site and poor prognosis. 14,17 This morphologic variant may present initially at diagnosis 16 or as a feature of disease progression. 18 Aberrant expression of T-cell antigens has also been rarely described in cases with the plasmablastic transformation of PCM, and it has been postulated that EBV may stimulate T-cell antigen expression in B-lineage neoplasms.…”
Section: Discussion Aberrant Expression Of Differentiation Markers Of a Different Cell Lineage On The Malignantmentioning
confidence: 99%
“…They can mimic high-grade lymphoma or non-hematopoietic malignancy by morphology [ 15 ]. The cells often resemble dysplastic megakaryocytes or giant cell osteoclasts [ 16 ]. In this case, the initial panel including CD3, CD20, CD138, and AE1/3 were all negative.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 Penelitian oleh Elsabah dkk juga menemukan hiperkalsemia dan peningkatan kreatinin pada pasien PCM. 10 Berbeda dengan kepustakaan, pada kasus ini hanya sedikit peningkatan kreatinin, tidak ada hiperkalsemia, hipoalbuminemia maupun leukopenia dan trombositopenia. Laporan kasus oleh Gupta dkk menemukan 25% PCM dengan insufisiensi renal serta 0% hiperkalsemia dan hipoalbuminemia.21 Sejalan dengan penelitian oleh Sudandyo dkk, ditemukan hanya 4% hiperkalsemia pada pasien PCM.…”
Section: Laporan Kasusunclassified